Antibiotic Susceptibility Profile in Urinary Tract Infection Patients at Tarakan Regional Hospital - Dharmawan, Ade; Wijaya, Pande I Gede Indra; Septiana, Yorisye; Pasaribu, Donna Mesina Rosadini; Tan, Henny Tannady; Simanjuntak, Lasma Susi F. (Muhammadiyah Medical Journal, 2024)
Background: Urinary tract infections (UTIs) are common in the community and hospital. In Indonesia, the incidence of UTI reaches 180,000 new cases per year. The most common pathogenic bacteria causing UTIs are dominated by Escherichia coli. Early empirical treatment of UTI cases can reduce morbidity. Knowing the pathogenic bacteria involved in urinary tract infections and their antimicrobial susceptibility patterns is necessary to provide appropriate empirical therapy. Purposes: Describe bacterial patterns and susceptibility profiles in urinary tract infection patients. Methods: A retrospective UTI dataset between 2019-2021whom admitted to Tarakan Regional General Hospital with a diagnosis of UTI. Resistance marker data for ESBL were obtained from the results of identification and resistance using the BD PhoenixTM Automated Microbiology System (Becton Dickinson, USA). The data was analyzed descriptively. Results: As many as 40 isolates were analyzed. Consist of E.coli (37.5%), Enterococcus faecium (20%) and Klebsiella pneumoniae (17.5%). The ESBL-producing E.coli bacteria rate reached 60%, while ESBL-producing K. pneumoniae reached 100%. Conclusion: E. coli was the most common pathogen, with the highest antibiotic sensitivity being imipenem, meropenem, and amikacin.